The Role of Fintech to Moderation and Cultural Values for Muslims - Wiwik Saidatur Rolianah; Ahmad Najib Fu'adi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2021)
In the digital economy, societies are developing service innovation in financial operations. As a result, financial technology, sometimes known as FinTech, evolved as a digital advancement in finance. In Indonesia, sharia FinTech is a type of financial technology that follows Islamic principles in its implementation. Moreover, the very presence of FinTech as a novel concept was awe-inspiring. Because Muslims make up the majority of Indonesia's population, the existence of FinTech as a new phenomenon was met with the value of moderation and Islamic culture. Is the acceptance of these ideas based on group disagreements between those who embrace and those who refuse a sort of religious moderation and culture that fosters tolerance. As a result, more investigation is required. As a result, more research is required in this area. Moreover, this study is descriptive qualitative, which means it describes the subject of the study. The findings reveal that financial product innovation has to do with responding to benefits and the global economy's dynamics. It is used to demonstrate that Islamic ideals can coexist with commercial competition and trade in the present era of globalization. It is used to demonstrate that Islamic ideals can coexist with commercial competitiveness and commerce in the current period of globalization and ensure business sustainability.